Dual-source powered sea urchin-like nanomotors for intravesical photothermal therapy of bladder cancer - Yixuan Mou; Zhenghong Liu; Wentao Xu; Bin Zheng; Minghai Ma; Xiaowen Qin; Jiajia Zheng; Ran Ni; Haichang Li; Lei Wang; Yuchen Bai; Jinhai Fan; et al. (Journal of Nanobiotechnology)
Abstract Bladder cancer (BCa) ranks as the 9th most prevalent malignancy worldwide, featured by its high risk of recurrence. Intravesical therapy constitutes the most important modality to tackle BCa, but its efficiency is often compromised due to the dense physiological barriers in BCa, the instability of the catalytic environment, and the rapid clearance facilitated by periodic urination. Here, we present a dual-source powered sea urchin-like nanomotor, which feature a gold nanocore decorated with ultrasmall platinum nanoparticles and ureases, enable rapid propulsion through the catalytic conversion of abundant urea and hydrogen peroxide present in the bladder cavity and BCa microenvironment, respectively. Our dual-source powered Au-Pt@ur NPs nanoparticles translocated across the mucus barrier rapidly, deeply penetrated tumor and hence chemo-resected bladder tumors in all cases. These results hold substantial promise for the development of biocompatible nanomotors for improved BCa intravesical therapy. Graphical abstract